2021
DOI: 10.48550/arxiv.2111.07700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Abelian T-duality of $AdS_{d\le3}$ families by Poisson-Lie T-duality

Ali Eghbali,
Reza Naderi,
Adel Rezaei-Aghdam

Abstract: We proceed to investigate the non-Abelian T-duality of AdS 2 , AdS 2 × S 1 and AdS 3 physical backgrounds, as well as two-sphere S 2 from the point of view of Poisson-Lie (PL) T-duality. To this end, we reconstruct these metrics of the AdS families as backgrounds of non-linear σ-models on two-and three-dimensional Lie groups. By considering the Killing vectors of these metrics and by taking into account the fact that the subgroups of isometry Lie group of the metrics can be taken as one of the subgroups of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Other examples are the PL T -duality of coset spaces, AdS2 and S 2 . Their PL T -dualities are discussed in this paper by using the general framework, but a recent paper [12] found that some two-dimensional group acts freely and transitively on a certain coordinate patch of AdS2 or S 2 . Then, we can perform the standard PL T -duality with respect to the two-dimensional isometry group.…”
Section: Dressing Cosetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples are the PL T -duality of coset spaces, AdS2 and S 2 . Their PL T -dualities are discussed in this paper by using the general framework, but a recent paper [12] found that some two-dimensional group acts freely and transitively on a certain coordinate patch of AdS2 or S 2 . Then, we can perform the standard PL T -duality with respect to the two-dimensional isometry group.…”
Section: Dressing Cosetsmentioning
confidence: 99%
“…It will be instructive to begin by considering a simple case where both (k â b ) = kā b , kib and ( kâ b ) = kā b , kib span the linear subspace g . 12 In this case, there is a matrix R ab (which gives a map g → g), that realizes 13…”
Section: And Accordingly We Introduce Constant Vectors {Kmentioning
confidence: 99%